La familia: una institución natural preexistente a la ley. Perspectivas sobre su regulación actual en España (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
The family is a natural institution, born spontaneously wherever there are humans. In most societies the family exists without state intervention and it is governed by traditional customs. Where the families exists the entire society grows and develops. The family is therefore the best natural environment in which the birth, upbringing, education, development of human life in all its stages, including death, are valued and protected. Marriage and the family are institutions of the utmost importance not only for individuals, but also for society. Legal and social protection institutions over marriage and the family causes benefits on them and the societies which protect them. The family is an institution which is found in all human societies.
Keywords: Marriage; Family; Institution; Natural order; Society; Law; State; Filiation